2017
DOI: 10.1021/acs.analchem.6b04315
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Peak Capacity in Nontargeted Omics Applications by Combining Full Scan Field Asymmetric Waveform Ion Mobility Spectrometry with Liquid Chromatography–Mass Spectrometry

Abstract: Full scan field asymmetric waveform ion mobility spectrometry (FAIMS) combined with liquid chromatography and mass spectrometry (LC-FAIMS-MS) is shown to enhance peak capacity for omics applications. A miniaturized FAIMS device capable of rapid compensation field scanning has been incorporated into an ultrahigh performance liquid chromatography (UHPLC) and time-of-flight mass spectrometry analysis, allowing the acquisition of full scan FAIMS and MS nested data sets within the time scale of a UHPLC peak. Proof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
(86 reference statements)
0
22
0
Order By: Relevance
“…Ion mobility separation was carried out at ambient pressure using a multichannel ultraFAIMS device with a 100-μm electrode gap, 78.1 mm trench length (span), and 700 μm ion path length [27]. The full CF range consisting of 19 steps from − 0.5 to 3.5 Td was acquired at rate 1 scan s −1 , at a fixed DF of 240 Td, suitable for metabolomics studies [25]. The FAIMS device was controlled by the prototype software FAIMS Control (Agilent Technologies, Santa Clara, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion mobility separation was carried out at ambient pressure using a multichannel ultraFAIMS device with a 100-μm electrode gap, 78.1 mm trench length (span), and 700 μm ion path length [27]. The full CF range consisting of 19 steps from − 0.5 to 3.5 Td was acquired at rate 1 scan s −1 , at a fixed DF of 240 Td, suitable for metabolomics studies [25]. The FAIMS device was controlled by the prototype software FAIMS Control (Agilent Technologies, Santa Clara, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The slow scan speed of the device did not allow the full CF range to be scanned within the timescale of an LC peak, so the FAIMS was stepped between six selected CFs, providing partial coverage of the metabolome. The hyphenation of hydrophilic interaction liquid chromatography (HILIC) with FAIMS-MS, using a miniaturised FAIMS device, was reported by Arthur et al [25], where a detailed comparison of the HILIC-MS and HILIC-FAIMS-MS analysis of urine showed that FAIMS integration into the analysis significantly increased the number of molecular features detected using 11 CF steps. Recently, Wernish et al [26] have published a study in which they analysed a mixture of more than 800 metabolites by 7 different chromatography columns.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the integration of IMS in LC–MS workflows introduces a third separation dimension that improves peak capacity and allows the separation of isobars and isomers [33]. The implementation of IMS in LC–MS workflows increase peak capacity at least 2 or 3-fold [34,35], although this improvement ultimately depends on IMS resolution and the analytical application. Moreover, chromatographic peaks are extracted from background noise which provides cleaned-up chromatograms and mass spectra, leading to an improvement of the limits of detection (LODs) and sensitivity.…”
Section: Overview Of Ion Mobility Spectrometry (Ims) Technique Andmentioning
confidence: 99%
“…Other notable recent studies have focused on nontargeted metabolomic assessment of placental samples , and serum profiling . The potential of LC–FAIMS–MS was also explored in a very recent contribution with a broad outlook toward different “omics” approaches .…”
Section: Application Of Ion Mobility Spectrometry To the Analysis Of mentioning
confidence: 99%